Evaluation of zinc oxide nanocomposites and L-ascorbic acid on meat quality during transport induced stress in birds of Sonali breed - ROY, M; SINGH, S K; BORKAR, S D; PARMAR, M S; PARVEEN, K; PRUSTY, S (The Indian Journal of Animal Sciences, 2024)
The study assessed the efficacy of phytofabricated zinc oxide nanoparticles (CF-ZnONPs) and L-ascorbic acid in alleviating pre-slaughter transport induced stress in birds of Sonali breed (Cross bred of Rhode Island Red cocks and Fayoumi hens). A total of 120 birds were divided into four groups: negative control (T1) which were loaded in vehicle but not transported, Positive control (T2) birds were transported without any prior supplementation, T3 and T4 birds were transported with prior supplementation (a day before transportation) of CF-ZnONPs @100 µg/ml and L-ascorbic acid @82 µg/ml in drinking water. Results obtained observed significant reduction in live weight, meat colour and pH but increased drip loss percentage in T2 group. Significantly elevated H/L ratio was recorded in all transported groups. Increased cortisol and TSH levels and decreased thyroid hormones, Triiodothyronine and thyroxin (T3 and T4) levels were recorded in T2 group. However, supplementation with CF-ZnONPs and L-ascorbic acid notably reversed these adverse effects, restoring meat quality and other metabolic profiles. Notably, ascorbic acid exhibited greater efficacy, suggesting its superior role in mitigating transportation-induced stress. Overall, these findings highlight the importance of antioxidant supplementation in alleviating transport induced stress in birds.